COMMUNITY PARTICIPATION IN MANAGING ABRASION IN MAPADEGAT BEACH IN THE DISTRICT OF NORTH SIPORA MENTAWAI ISLANDS - Januarti, Helni; Dasrizal, Dasrizal; Zuriyani, Elvi (STKIP PGRI Sumbar, 2013)
Â This study aimed to obtain information, analyze and describe data on community participation in tackling abrasion Mapadegat Beach in the District of North Sipora Mentawai Islands regency views of: 1) prohibit the participation of sand quarrying activity, 2) participation in reforestation and 3) participation preserve beach Mappadegat.This study is a qualitative study using interview techniques. To answer this problem used primary data and secondary data. Primary data was collected through observation, interviews, discussions with informants and photographs taken in the field, while the secondary data obtained from the relevant parties.Research results showed: (1) prohibit people want to participate in sand mining activities, but to date the sand mining is still running, (2) People want to participate in reforestation activities because they want the beauty and sustainability can be maintained Mappadegat da beach (3) Society willing to participate in conserving coastal Mappadegat be maintained